A Methodology for Developing Web-based CAD/CAM Systems: Case Studies on Gear Shaper Cutters - Malahova, Anna (Cranfield University, 2014)
The research establishes a methodology for developing Web-based CAD/CAM software systems to industrial quality standards in a time and cost e ective manner. The methodology de nes the scope of applicability, outlines major considerations and key principles to follow when developing this kind of software, describes an approach to requirements elicitation, resource allocation and collaboration, establishes strategies for overcoming uncertainty and describes the design concerns for industrial Web-based CAD/CAM systems. The crucial parts of the methodology are a novel project development model facilitating architecture optimisation early in the project to minimise total development e orts, create future-proof solutions and ensure system maintainability; and a novel approach for planning based on time reserve management and task prioritisation, which provides the exibility required for exploratory development while maintaining the main focus on project objectives. The e ectiveness of the Web-based CAD/CAM software development methodology has been examined using two real software development case studies: a Web-based CAD/CAM system for involute spur gear shaper cutters and a Web-based CNC code editor for online modi cation of the pro le for manufacturing gear shaper cutters. The development of case studies using the established methodology resulted in on-time delivery of two industrial browser-based CAD/CAM systems, that produce valid results, embrace all business processes associated with the application area, ensure all functional and non-functional requirements and are used in production now. The developed software products demonstrate robustness, performance, reliability, security and usability comparable with the standards of modern commercial software, utilise advantages of Web-based applications to the highest extent and con rm advantages of Web-based CAD/CAM software compared to similar desktop applications. E ectiveness of the proposed methodology for Web-based CAD/CAM software development was checked through validation, evaluation and analysis of case study results.